Influencia de la calidad de vida en los trabajadores y en la influencia de la calidad de vida en los trabajadores y en la organización (2021)
Through the application of a simple battery, it is possible to identify what workers want, how it influences the quality of life in their day to day and improves productivity in organizations. How workers identify a series of benefits which influence their environment and improve their level of work, loyalty, health and well-being.